The oxytocin receptor represents a key hub in the GPCR heteroreceptor network: potential relevance for brain and behavior - Borroto-Escuela, Dasiel O.; Cuesta-Marti, Cristina; Lopez-Salas, Alexander; Chruścicka-Smaga, Barbara; Crespo-Ramírez, Minerva; Tesoro-Cruz, Emiliano; Palacios-Lagunas, Daniel A.; Perez de la Mora, Miguel; Schellekens, Harriët; Fuxe, Kjell (Frontiers in Molecular Neuroscience, 2022)
In the last 10 years, it has become increasingly clear that large numbers of axon collaterals extend from the oxytocin (OXT) hypothalamic axons, especially the parvocellular components, to other brain regions. Consequently, the OXT signaling system forms, like other monoamine axons, a rich functional network across several brain regions. In this manuscript, we review the recently indicated higher order G-protein coupled heteroreceptor complexes of the oxytocin receptor (OXTR), and how these, via allosteric receptor-receptor interactions modulate the recognition, signaling, and trafficking of the participating receptor protomers and their potential impact for brain and behavior. The major focus will be on complexes of the OXTR protomer with the dopamine D2 receptor (D2R) protomer and the serotonin 2A (5-HT2AR) and 2C (5-HT2CR) receptor protomers. Specifically, the existence of D2R-OXTR heterocomplexes in the nucleus accumbens and the caudate putamen of rats has led to a postulated function for this heteromer in social behavior. Next, a physical interaction between OXTRs and the growth hormone secretagogue or ghrelin receptor (GHS-R1a) was demonstrated, which consequently was able to attenuate OXTR-mediated Gαq signaling. This highlights the potential of ghrelin-targeted therapies to modulate oxytocinergic signaling with relevance for appetite regulation, anxiety, depression, and schizophrenia. Similarly, evidence for 5-HT2AR-OXTR heteromerization in the pyramidal cell layer of CA2 and CA3 in the dorsal hippocampus and in the nucleus accumbens shell was demonstrated. This complex may offer new strategies for the treatment of both mental disease and social behavior. Finally, the 5-HT2CR-OXTR heterocomplexes were demonstrated in the CA1, CA2, and CA3 regions of the dorsal hippocampus. Future work should be done to investigate the precise functional consequence of region-specific OXTR heteromerization in the brain, as well across the periphery, and whether the integration of neuronal signals in the brain may also involve higher order OXTR-GHS-R1a heteroreceptor complexes including the dopamine (DA), noradrenaline (NA) or serotonin (5-HT) receptor protomers or other types of G-protein coupled receptors (GPCRs).